The language of land and water a linguistic analysis of conceptual metaphors in selected poems of Conchitina R. Cruz - Esperas, Yvonne M. (c2004.)
This study focuses on the concept of imagery within the pureview of Gary Palmer's framework for Cultural Linguistics. In this aspect, the poems that are written in English by Conchitina R. Cruz (a young Filipino female writer) are analyzed using the cognitive model of George Lakoff and Mark Johnson on metaphorical concept and orientational metaphors, cognitive model of Zoltan Kovecses on ontological metaphors. Specifically, the analysis focuses on the frequently recurring land and water metaphors in selected poems of Cruz. As a whole, given the nature of metaphors and the status of Cruz as a post-colonial Filipino writer, this study attempts to present how metaphorical concepts in the English language manifest a writer's Philippine world view, which are shared by the rest of the Philippine society.
Thesis (M.A. English Studies : Language)--University of the Philippines Diliman.
Keywords: Cruz, Conchitina R; Linguistic analysis (Linguistics); Philippine poetry (English)